Konstruksi Pemikiran Madzhab Asy’ari dalam Tafsir Jalalain - Muhammad Ikhsanul Faqih (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
Tafsir Jalalain is one of the most widely studied commentaries in Indonesia. Thiscommentary was written by two commentators, namely Jalaluddin al-Mahalli andJalaluddin as-Suyuthi. Both are adherents of the Ash'ariyah school of thought interms of theological thinking. So that in interpreting the verses related to faith, bothtend to follow what is taught by the Asy'ariyah school. This can be seen in severalverses relating to the main discussion in the Asy'ariyah teachings as well as in themutasayabihat verses, the verses about seeing Allah, the verses about the position ofpeople who commit major sins and other verses related to them. In these verses,these two commentators provide explanations that are not much different from whatis taught by the Asy'ariyah school. Of course with a concise and global explanation.